Common nonsynonymous substitutions in SLCO1B1 predispose to statin intolerance in routinely treated individuals with Type 2 diabetes: A Go-DARTS study - Donnelly, L; Doney, A; Tavendale, R; Lang, C; Pearson, E; Colhoun, H; McCarthy, M; Hattersley, A; Morris, A; Palmer, C (2011)
SLCO1B1 gene variants are associated with severe statin-induced myopathy. We examined whether these variants are also associated with general statin intolerance in a large population of patients with type 2 diabetes receiving statins as part of routine clinical care. A total of 4,196 individuals were genotyped for rs4149056 (Val174Ala) and rs2306283 (Asp130Asn). Intolerance was defined by serum biochemistry and also by discontinuation, switching, or reduction in dose of the prescribed statin drug. Ala174 was associated with higher intolerance (odds ratio = 2.05, P = 0.043), whereas Asp130 was associated with lower intolerance (odds ratio = 0.71, P = 0.026). Ala174 was associated with a lower low-density lipoprotein cholesterol (LDLc) response to statins (P = 0.01) whereas 130D was associated with a greater LDLc response to statins (P = 0.048), as previously reported; however, this association was no longer present when data for statin-intolerant individuals were removed from the analysis. This study suggests that common genetic variants selected for an extreme phenotype of statin-induced myopathy also predispose to more common milder statin intolerance and may, for this reason, impact lipid-lowering efficacy. © 2011 american Society for Clinical Pharmacology and Therapeutics.